POLITENESS STRATEGIES APPLIED IN THE DIRECTIVE SPEECH ACT IN THE DA VINCI CODE AND ITS TRANSLATION - Sumardiono, Sumardiono (Universitas Sebelas Maret, 2014)
This research aims at identifying what and how politeness strategies are applied in the directive speech act in The Da Vinci Code and how they are transfered into their translation. There are twenty four data gained from chapter one to chapter twenty of the novel. First, the researcher identify the directive speech act in The Da Vinci Code, the utterances then classified based on the politeness strategy applied in the context. In the analysis the utterances are described based on the situational context. The analysis also explain why the speaker apply the strategy. The strategy used in the source text is then compared with that in the source text. There are some conclussions derived; only three strategies propossed by Brown and Levinson were apllied in the directive speech act. They are bald on record, positive politenss and negative politeness. There is no off record strategy applied in the data. The same communicant (the speakers and hearers) applied different strategies in different situation, meaning that there is no single strategy applied to similar interlocutors at anytime.All the strategies applied in the source text are transferred exactly into the same strategies in the target text. There is no strategy shift found.